The Application of Energy Saving Technology in High Rise Building a Lanzhou - Feng, Shangsu; A., Zulkiple (2013)
Most of designers focus on pursuit of face and the use of functional form, but ignored environmental protection and energy saving, lead to high energy consumption, wasting a lot of resources and properties, and low efficiency. Energy-saving technology can effectively prevent these defects in high-rise buildings, protect the environment, and reduce waste and pollution in build high-rise buildings. It is not only benefiting the city's construction and rational use of resources but also energy as a new technology for high-rise buildings.